2016
DOI: 10.3171/2015.6.jns15622
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of the frontal and anterior insular network: a cortico-cortical evoked potential study

Abstract: OBJECT The frontal and insular fiber network in humans remains largely unknown. This study investigated the connectivity of the frontal and anterior insular network in humans using cortico-cortical evoked potential (CCEP). METHODS This retrospective analysis included 18 patients with medically intractable focal epilepsy who underwent stereoelectroencephalography and CCEP. Alternating 1-Hz electrical stimuli were delivered to parts of the frontal lobe and anterior insula (prefrontal cortex [PFC], ventrolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
(28 reference statements)
2
20
0
Order By: Relevance
“…Analysis of corticocortical evoked potential (CCEP) has demonstrated epileptic networks 35,36 in patients with focal epilepsy. Analysis of corticocortical evoked potential (CCEP) has demonstrated epileptic networks 35,36 in patients with focal epilepsy.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of corticocortical evoked potential (CCEP) has demonstrated epileptic networks 35,36 in patients with focal epilepsy. Analysis of corticocortical evoked potential (CCEP) has demonstrated epileptic networks 35,36 in patients with focal epilepsy.…”
Section: Limitationsmentioning
confidence: 99%
“…Stereotactic EEG has the potential to delineate subcortical electrophysiological activity in ES in the future. Analysis of corticocortical evoked potential (CCEP) has demonstrated epileptic networks 35,36 in patients with focal epilepsy. There are no reports investigating ES using CCEP.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, a small number of studies have provided electrophysiological evidence of a monosynaptic connection between IFG and medial superior frontal gyrus (Enatsu et al, 2016;Matsumoto et al, 2007;Ookawa et al, 2017;Swann et al, 2012). Enatsu and colleagues (2016) investigated 18 patients using cortico-cortical evoked potentials (CCEP) and found that stimulation of the pre-SMA induces a robust response in IFG.…”
Section: Anatomy and Connectivity Of The Frontal Aslant Tractmentioning
confidence: 99%
“…In CCEPs, stimulation frequencies such as 1 Hz, 0.5 Hz, 0.33 Hz, 0.2 Hz, 0.1 Hz, and 0.067 Hz have been used in the past (Table ). Only one study has looked at effects of stimulation frequency on response morphology— little difference in responses to 2 and 1 Hz stimulation in Heschl's gyrus was shown; however, there was a marked change between 2 and 5 Hz …”
Section: Physical Stimulation Considerationsmentioning
confidence: 99%
“…Monophasic pulses have been shown to be efficient AP generators, but have shown to be more damaging than charge‐balanced waveforms . Alternating monophasic waveforms have been used in many CCEPs studies, both in SEEG and ECoG; these waveforms are able to efficiently generate APs, reverse many electrochemical reactions and simultaneously mitigate stimulation artifact when averaged. Monophasic pulses may also produce different physiologic effects.…”
Section: Physical Stimulation Considerationsmentioning
confidence: 99%